Study of Naturally Woven Coconut Leaf Sheath-Reinforced Polypropylene Matrix Based Composites - Pinku Poddar; Kamol Dey; Sumon Ganguli; Shahin Sultana; Husna Parvin Nur; A. M. Sarwaruddin Chowdhury (The Journal of Pure and Applied Chemistry Research, 2018)
Renewable materials have gained significant attraction as reinforcement in polymer matrix composites. Naturally woven coconut leaf sheath (CLS) fiber-reinforced polypropylene (PP) composites were prepared by compression molding. Different composites were fabricated varying the weight percentage of CLS fiber (5, 10, 15, 20 and 25 wt%) . Hydrophilic nature of the CLS fiber was evaluated using water uptake test. Structural feature of the composites was confirmed by infrared spectroscopy. Mechanical performance was investigated using tensile and bending tests. Fiber reinforcement significantly increased the mechanical properties of the composites. Moreover, thermal properties and degradation nature of the composites were investigated.